Kurrikulering vir die omvattende generiese verpleegkundeprogram - L.R. Uys (AOSIS, 1983)
The six stages of curriculum-development are discussed briefly with the new comprehensive nursing program in mind. The problems encountered in the first stage, situation analysis, are identified and the use of objectives in the total curriculum discussed. The different patterns of curriculum organisation are described and selection of content, methods and techniques briefly referred to. The importance of evaluation as the last stage of curriculum development is shown.